2020
DOI: 10.3389/fmats.2020.00061
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Conductivity of Cell-Laden Alginate Microfibers With Aqueous Graphene for Neural Applications

Abstract: Microfluidically manufacturing graphene-alginate microfibers create possibilities for encapsulating rat neural cells within conductive 3D tissue scaffolding to enable the creation of real-time 3D sensing arrays with high physiological relavancy. Cells are encapsulated using the biopolymer alginate, which is combined with graphene to create a cell-containing hydrogel with increased electrical conductivity. Resulting novel alginate-graphene microfibers showed a 2.5-fold increase over pure alginate microfibers, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 52 publications
(76 reference statements)
0
28
0
Order By: Relevance
“…[16] Its structure of M- and G-blocks can be ionically crosslinked in the presence of divalant cations, such as Ca 2+ , Ba 2+ , Sr 2+ , and others; however, calcium crosslinkers are commonly used in biomedical applications because they are readily available and cost effective, and because calcium alginate hydrogels exhibit good swelling properties, which is important to maintain cell viability. [5, 6, 9, 35]…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[16] Its structure of M- and G-blocks can be ionically crosslinked in the presence of divalant cations, such as Ca 2+ , Ba 2+ , Sr 2+ , and others; however, calcium crosslinkers are commonly used in biomedical applications because they are readily available and cost effective, and because calcium alginate hydrogels exhibit good swelling properties, which is important to maintain cell viability. [5, 6, 9, 35]…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, the microfluidic channel features a main chamber which has dimensions of 130 μm x 390 μm, which holds four chevrons to allow for lateral shaping of the core fluid. [6, 9, 29, 30, 32] These chevrons are 200 μm apart and have dimensions of 130 μm x 100 μm.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, they found that hydrophilic graphene did not exhibit the harmful traits that hydrophobic graphene possessed. They concluded that surface functionalization is one of the salient factors that mitigate the cytotoxic characteristics of pristine graphene [62][63][64]. Since the hydrophobic portion of BSA is adsorbed on graphene, the hydrophilic part interacts with water and the surrounding environment promoting a benign interaction with cells.…”
Section: Integration Of Bovine Serum Albumin Few-layer Graphene With mentioning
confidence: 99%